How do you solve the system -3(5+x)=y and 5(x-3)=2y+4?

1 Answer
Jul 7, 2015

Answer:

#(x,y) = (-1,-12)#

Explanation:

Given:
[1]#color(white)("XXXX")##-3(5+x)=y#
[2]#color(white)("XXXX")##5(x-3)=2y+4#

Replace #y# in [2] with #-3(5+x)# as specified in [1]
[3]#color(white)("XXXX")##5(x-3)=2(-3(5+x))+4#

Simplifying
[4]#color(white)("XXXX")##5x-15 = -30-6x+4#
[5]#color(white)("XXXX")##11x = -11#
[6]#color(white)("XXXX")##x = -1#

Substituting #x=-1# back in [1]
[7]#color(white)("XXXX")##-3(5-1) = y#
[8]#color(white)("XXXX")##y = -12#